LOCALWISDOM OF SOCIETY IN THE SELECTIONOFWOOD TYPE ASJALUR IN PEBAUN HULU KECAMATANKUANTAN MUDIKKABUPATEN KUANTAN SINGINGI - Raja Febrianto; M. Mardhiansyah M. Mardhiansyah; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Kabupaten Kuantan Singingi has a culture that is still maintained until now that is pacujalur. The culture of pacu jalur is a tradition to celebrate the anniversary of independence of the Republic of Indonesia. Jalur is a long boat made of wood which contains 40 to 60 children race. Selection of wood types ofjalur is a culture that is not less important where the selection of the type of wood as jalur in the village Pebaun Hulu is also a tradition that has hereditary. The purpose of this study was to determine how the local wisdom of villagers Pebaun Hulu in choosing the type of wood, wood and manufacture of wood criteria to track materials. Wood type the jalur used by village communities Pebaun Hulu is red meranti wood and banio. The criteria selected wood by societies that long 20 to 30 meters, diameter of 1 to 2 meters, the straightness of 90 to 100% and do not have a foul or knots. Keywords:pacu jalur, wood type selection, wood criteria, local wisdom